(3GdhUjI GdeHGQcI GdaGFbI hGdfUjMI GdUMjMI GdQGFbIs - (3SjOj GdeNJGQ Hf GdgjHI GdGfJTGFj,J (B1285 (3g` s ((3VjGA GdOjf eMeO Hf eMeO Hf GdMUf s)
(3ChdgG (B:s
(3GdMeO ddg Pi GdaVd GdYXje hGdcQe GdeJaVd Ydi NhGU YHjOg HGdUHQ hGdQVi hGdJSdje hQaYI Gdgee hHYO aGYde Cf ecJhHc GdeHfi Yf eWdhHc hUd EdjfG Ke dJYde (B_ (3SOOfi Gddg hCjOc Ef GdCYOGA GdCQHYI GdJi gi (B: (3GdfaS hGdTjWGf hGdghi hGdOfjG dGHO ddeQs
(3BNQgG (B:s
(3hGYde (B_ (3CjOc Gddg (B_ (3Cf CUhd GdNjQ cdg NeSI (B: (3Ydh GdgeI hfahR GdYRjeI hMSf GdNOeI hMaX GdMQeI hTcQ GdfYeI hef JQc hGMOI ef gPg abO CYhRg Jhajbg hGfYOe JMbjbg EfJgJ GdhUjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeI JGeI heUMMIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs